Growth dynamics of solid electrolyte interphase layer on SnO2 nanotubes realized by graphene liquid cell electron microscopy. (July 2016) - Cheong, Jun Young; Chang, Joon Ha; Seo, Hyeon Kook; Yuk, Jong Min; Shin, Jae Won; Lee, Jeong Yong; Kim, Il-Doo
Abstract: Formation of stable solid electrolyte interphase (SEI) layer is critical to outstanding performance of energy storage devices, because it acts as a passive layer that allows facile transport of ions but forbids electron transport between the electrolyte and electrode. Although much study has been devoted to investigate the morphology and structure of SEI layer using a myriad of analytical devices on past decades, the direct observation of SEI layer on a real time scale has remained as a formidable challenge. In addition, it has been difficult to observe both the decomposition of electrolytes and formation process of stable SEI layer at nanometer scale. Here we utilize in situ transmission electron microscopy (TEM) using graphene liquid cell (GLC) to realize the observation of stable SEI layer formation in a sequential time scale. Upon e − beam irradiation, Li salts in the electrolytes react with reduced electrolytes and form gel-like agglomerates, which are deposited on the surface of the active material as a passivation layer and later stabilized to become more uniform in overall thickness. Additionally, growth dynamics of stable SEI layer were suggested, where the deposition of decomposed electrolytes eventually result in relatively uniform SEI layer. This paper demonstrates that it is possible to observe not only the formation of non-crystalline SEI layer but also the movement of decomposed electrolytes onto the surface of active materials which account for broader understanding of SEI layer, and has the potential to detect important interfacial phenomena in electrochemical devices that were overlooked so far. Graphical abstract: In situ TEM observation of deposition of decomposed electrolytes and formation of SEI layer on active material was successfully realized using GLC. From in situ TEM observations, growth model of SEI layer has also been suggested, which provides more insight on growth dynamics of SEI layer. Highlights: First study has been executed for in situ TEM analysis using graphene liquid cell, not SiNx window, to observe the growth of stable solid electrolyte interphase layer of SnO2 nanotubes. Growth of solid electrolyte interphase layer has been observed, with higher resolution. Realistic in situ observation has been conducted, in agreement with the ex situ TEM image. Growth dynamics of solid electrolyte interphase has been clearly visualized, which opens up new opportunities to observe different interfacial phenomena through graphene liquid cell.